Kajian Kondisi Ruang Terbuka Hijau (RTH) Di Kelurahan Lai Lai Bisi Kopan (LLBK) Kota Kupang - Lay, Yermias Elvis; Effendi, Jauhari; Ramang, Ruslan (Fakultas Teknik, Universitas Brawijaya, 2014)
Open green spaces for urban people who live in city is something that cannot be separated with their lives. The importance of open green spaces could support the aesthetic value and beauty open green spaces and also provide a cooler micro-climate by maintaining the balance of oxygen and carbon dioxide, reducing pollutants and help maintain availability of ground water. Based on the existing problems, the researcher tries to analyze how the conditions of the existing open green spaces in the LLBK Village Kupang today, and how the concept of green spaces planning is needed in the LLBK Village Kupang. The research is conducted in the LLBK Village for four months from August to December 2013. Data collecting techniques used in this study is field observation to obtain secondary data and primary data, while the data analysis techniques used in this study is a descriptive analysis under the qualitative paradigm. The result of the analysis showed the arrangement of open green spaces in LLBK village faces a number of problems due to the LLBK village as economic/trading center, coastal areas, the old town and cultural heritage. The development of facilities and infrastructure needs resulting in an area of open green space that is difficult to develop. Based on the results of observations, it is known that there is open green space at LLBK consists of Kopan coastal city park, open parking in Siliwangi road, coastal border, and a roof garden with a total area of 0.74 ha reaches 6.38% or urban at the total of LLBK area of 11.6 hectares or 116,000 m 2 . The concept of open green spaces planning in LLBK is analyzed based on the following components: 1) The principle of the physical environment that includes vegetation, soil, and water. 2) The principle ingredients include: pedestrian, vehicle lanes, parking lots, building support, signs (signage), open space, landscape equipment, network utilities. 3) Management Principles and Design include: construction of protection, utility management. While the type of open green spaces can be developed consisting of public open green spaces (city park, coastal town, open road parking Siliwangi, coastal border) and private open green spaces (courtyard house, roof garden, office) to improve environmental quality in the area as well as contributing collectively to open green spaces.Keywords: open green spaces, old city.